Retirement, Wages, and Labor Supply of the Elderly - Hanoch, Giora; Honig, Marjorie (Journal of Labor Economics, 1983)
A model of labor force participation, market wages, and labor supply of annual hours and weeks of work is estimated for married males and unmarried females in a sample from the retirement history survey, 1969-75, matched with social security earnings records. Emphasis is placed on the effects of variables associated with retirement and old age and on the estimation of net age profiles purged of biases associated with specific years and cohorts and with the other included variables. The effects of most of the usual variables appear to be consistent with the theory and with other empirical findings for both sexes. In addition, age itself has a strong net autonomous effect on each of the dependent variables due to biological, societal, or institutional factors.